Directed Evolution Library Creation Methods and Protocols - Gillam, Elizabeth M.J.; Gillam, Elizabeth M.J.; Copp, Janine N.; Copp, Janine N.; Ackerley, David.; Ackerley, David. (Methods in Molecular Biology,, 2014)
Directed Evolution Library Creation: Methods and Protocols, Second Edition presents user-friendly protocols for both proven strategies and cutting-edge approaches for the creation of mutant gene libraries for directed evolution. As well as experimental methods, information on current computational approaches is provided in a user-friendly format that will allow researchers to make informed choices without needing to comprehend the full technical details of each algorithm. Directed evolution has become a fundamental approach for engineering proteins to enhance activity and explore structure-function relationships, and has supported the rapid development of the field of synthetic biology over the last decade. Divided into three convenient sections, topics include point mutagenesis strategies, recombinatorial methods wherein genetic diversity is sourced from multiple parental genes that are combined via either homology-dependent or -independent techniques, and a variety of computational methods to guide the design and analysis of mutant libraries. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Directed Evolution Library Creation: Methods and Protocols, Second Edition will serve as a reliable manual for both novice and experienced protein engineers and synthetic biologists and will enable further technical innovation and the exploitation of directed evolution for a deeper understanding of protein design and function.